Pregnancy and neonatal complications in women with polycystic ovary syndrome in relation to second-trimester anti-Müllerian hormone levels. Issue 1 (July 2019) - Valdimarsdottir, Ragnheidur; Valgeirsdottir, Heiddis; Wikström, Anna-Karin; Kallak, Theodora Kunovac; Elenis, Evangelia; Axelsson, Ove; Ubhayasekhera, Kumari; Bergquist, Jonas; Piltonen, Terhi T; Pigny, Pascal; Giacobini, Paolo; Poromaa, Inger Sundström
Abstract: Research question: An association has been found between high anti-Müllerian hormone (AMH) levels during pregnancy and the development of polycystic ovary syndrome (PCOS)-like phenotypic traits in mouse offspring. The aim of this study was to determine whether AMH levels are associated with maternal testosterone levels, and whether high AMH concentration influences the risk of developing PCOS-related adverse pregnancy outcomes. Design: Maternal serum AMH, testosterone and sex hormone binding globulin levels were measured in blood samples taken in early second-trimester pregnancies from women with PCOS ( n = 159) and healthy controls matched for body mass index ( n = 320). Possible associations with preeclampsia, gestational hypertension, gestational diabetes, preterm birth and birthweight was explored by logistic and linear regression models. Results: Women with PCOS had higher AMH, higher total testosterone levels and higher free androgen index than controls ( P < 0.001 for all three parameters). Among women with PCOS, high testosterone levels (B = 2.7; β = 0.26; P = 0.001) and low first trimester body mass index (B = –0.5; β = –0.17; P = 0.043) remained independently associated with AMH. High AMH levels were associated with decreased risk of gestational hypertension (adjusted OR 0.55; 95% CI 0.34 to 0.87), but no association was found with other adverse pregnancy outcomes or birthweight. Conclusions: Women with PCOS had higher AMH levels during pregnancy compared with controls, but high AMH was not associated with increased risk of adverse pregnancy outcomes or birthweight.